Time delays in treatment of snakebite patients in rural Sri Lanka and the need for rapid diagnostic tests. - Anjana Silva; Jiri Hlusicka; Nipuna Siribaddana; Subodha Waiddyanatha; Senaka Pilapitiya; Prasanna Weerawansa; Niroshan Lokunarangoda; Sujeewa Thalgaspitiya; Sisira Siribaddana; Geoffrey K Isbister (Public Library of Science (PLoS), 2020)
Delays in treatment seeking and antivenom administration remain problematic for snake envenoming. We aimed to describe the treatment seeking pattern and delays in admission to hospital and administration of antivenom in a cohort of authenticated snakebite patients. Adults (> 16 years), who presented with a confirmed snakebite from August 2013 to October 2014 were recruited from Anuradhapura Hospital. Demographic data, information on the circumstances of the bite, first aid, health-seeking behaviour, hospital admission, clinical features, outcomes and antivenom treatment were documented prospectively. There were 742 snakebite patients [median age: 40 years (IQR:27-51; males: 476 (64%)]. One hundred and five (14%) patients intentionally delayed treatment by a median of 45min (IQR:20-120min). Antivenom was administered a median of 230min (IQR:180-360min) post-bite, which didn't differ between directly admitted and transferred patients; 21 (8%) receiving antivenom within 2h and 141 (55%) within 4h of the bite. However, transferred patients received antivenom sooner after admission to Anuradhapura hospital than those directly admitted (60min [IQR:30-120min] versus 120min [IQR:52-265min; p<0.0001]). A significantly greater proportion of transferred patients had features of systemic envenoming on admission compared to those directly admitted (166/212 [78%] versus 5/43 [12%]; p<0.0001), and had positive clotting tests on admission (123/212 [58%] versus 10/43 [23%]; p<0.0001). Sri Lankan snakebite patients present early to hospital, but there remains a delay until antivenom administration. This delay reflects a delay in the appearance of observable or measurable features of envenoming and a lack of reliable early diagnostic tests. Improved early antivenom treatment will require reliable, rapid diagnostics for systemic envenoming.